Movement and Space Use of Grass Carp in the Sandusky River, Ohio: Implications for Lake Erie Eradication Efforts. (21st March 2021) - Harris, Cleyo; Brenden, Travis O.; Vandergoot, Christopher S.; Faust, Matthew D.; Herbst, Seth J.; Buszkiewicz, John T.; Nathan, Lucas R.; Fischer, Jason L.; Krueger, Charles C.
Abstract: The Grass Carp Ctenopharyngodon idella is an invasive species to the Laurentian Great Lakes that was first detected in the 1980s. The western basin of Lake Erie is the putative invasion front for the Great Lakes, with spawning known to occur in two of the basin's tributaries (Sandusky and Maumee rivers). Targeted removal is being used to reduce Grass Carp abundance, with an ultimate aim of eradication in part to prevent spread and establishment in the other Great Lakes; response efforts are being concentrated in the Sandusky River due to its heavy use by Grass Carp and because it is the tributary where spawning occurs consistently. The goal of this research was to identify areas in the Sandusky River where Grass Carp aggregate and identify variables that influence movement to improve efficiency of response efforts. Movement and space use of 27 Grass Carp were monitored using acoustic telemetry. Detection data were used to estimate movement and daily detection rates and also used in a spatial capture–recapture model to estimate activity centers of tagged fish. Grass Carp movement was highest when daily discharge and water temperature exceeded 31 m 3 /s and 18°C, respectively, and next highest when discharge exceeded 31 m 3 /s and temperature was between 4.5°C and 18.0°C. Daily detection rates at receivers and concentrations of activity centers suggested that aggregations occurred between river kilometers (RKMs) 34 and 36 and at RKM 45. During spawning conditions, Grass Carp also aggregated near RKM 48.6, which is proximal to suspected spawning locations. We recommend concentrating response efforts in these general locations and using passive capture gear when Grass Carp are the most mobile. Response efforts could be further refined by using a variety of acoustic telemetry monitoring techniques, including fine‐scale positioning, real‐time receivers, and mobile tracking to provide precise location and timing for removal actions.